PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO TERHADAP PENGETAHUAN TENTANG SEX ABUSE PADA ANAK SEKOLAH DI SDN MERJOSARI 4 KOTA MALANG - Neni Maemunah; Wahidyanti Rahayu Hastutiningtyas; Megiwati Inka Wello (STIKes Maharani Malang, 2023)
Health education on sex abuse in children requires interesting media. One of the interesting media for children is video media. Videos provide clear and concise information as well as moving images so that they can attract sympathetic children to watch. To determine the effect of health education using video media on knowledge about sex abuse in school children at SDN Merjosari 4 Malang City. The research design used a pre-experimental research design with a one group pretest-posttest design. The population of this study were all school children at SDN Merjosari 4 Malang City. There were 84 school children with a total sample of 69 children. Samples were taken by simple random sampling technique. The independent variable is health education with video media, the dependent variable is knowledge about sex abuse. The instruments used are SAP videos and questionnaires. Data analysis used the marginal homogeneity test. Showed that before being given health education, almost half of the children had knowledge about sex abuse in the poor category of school children at SDN Merjosari 4 Malang City, after being given health education most of the children had knowledge about sex abuse in the good category for school children at SDN Merjosari 4 Malang City and there is the effect of health education using video media on knowledge about sex abuse in school children at SDN Merjosari 4 Malang City. The results of cross-tabulation show that before being given health education about sex abuse, the knowledge of school children is in the less category and after being given health education about sex abuse, the knowledge of school children is in the good category, so that the better the knowledge and awareness of a person to maintain dental hygiene, the more clean his teeth will be. It is hoped that further research will be able to examine work, experience, culture and the surrounding environment as factors that influence knowledge. Keyword: Sex Abuse, Health Education, and Video Media